Public Policy In Addressing Ikhtikar Practices In Indonesia's Digital Market Ecosystem - Syahidah Rahmah (Universitas Cahaya Prima, 2024)
This study examines how the rapid development of the digital economy has transformed market structures in Indonesia while simultaneously creating new challenges in the form of digital monopolistic practices characterized by the concentration of data, algorithms, and network effects among large digital platforms. The study aims to analyze the relevance of digital monopoly practices to the concept of ihtikar in Islamic economics, identify the limitations of existing public policies in addressing platform dominance, and formulate the Digital Hisbah Framework as an alternative policy model. Employing a qualitative normative-descriptive approach with a library research method, the study draws data from competition law regulations, digital economy policies, and Islamic economic literature. The collected data were analyzed using content analysis and comparative policy analysis. The findings reveal that digital monopoly practices share substantial similarities with the concept of ihtikar, as both involve the concentration and control of economic resources that may restrict market access, hinder fair competition, and undermine public welfare. Furthermore, Indonesia’s current competition policy framework still faces significant limitations in addressing algorithmic manipulation, data concentration, and the increasing dependence of micro, small, and medium enterprises (MSMEs) on digital platforms. Based on these findings, the study proposes the Digital Hisbah Framework, which integrates the principles of al-hisbah, market justice, transparency, equitable data governance, and MSME protection into the supervision of digital markets. This framework is expected to provide a more adaptive policy model for fostering a fair, transparent, competitive, and public welfare-oriented digital ecosystem.